Changes in Mechanical Properties of Ultrahigh Strength Nanostructured Steel Resulting from Repeated High Strain Rate Deformation - Jarosław MARCISZ (Zmiany właściwości mechanicznych ultrawytrzymałej stali nanostrukturalnej w wyniku wielokrotnego odkształcenia dynamicznego, 2019)
The paper contains results of investigation of nanostructured bainitic steel subjected to repeated high-strain-rate deformations using split Hopkinson pressure bar method and uniaxial compression of cylindrical specimens in Gleeble simulator. Steel of chemical composition Fe-0.58%C-1.80%Si-1.95%Mn-1.3Cr-0.7Mo (weight %), after isothermal heat treatment at 210°C, is characterized by following mechanical properties determined at static tensile test: yield strength YS0.2 = 1.3 GPa; ultimate tensile strength UTS = 2.05 GPa; total elongation E = 12%, hardness 610 HV and Charpy-V impact toughness 24 J at +20℃ and 14 J at -40℃. Stress-strain curves obtained for pre-stressed material before the next dynamic compression and after repeated compressions were analysed. Microstructure of the deformed specimens in areas of the dynamic impact was investigated. The effects of the dynamic repeated impact on changes in characteristics of the investigated material, in that on strain hardening mechanism, were established. Critical strains of 5.3% at strain rate 910 s-1 and about 10% at strain rate 50 s-1 for the nanostructured bainite were determined. Exceeding the critical strain under uniaxial repeated high-strain-rate compression, resulted in decreasing of ability of the steel for further plastic deformation and strain hardening.
Keywords: Właściwości mechaniczne ultrawytrzymałej stali nanostrukturalnej